Efficiency Evaluation of Various Solvents in Retreatment of Endodontic Filling in Extracted Teeth - Adriana Katunarić; Petra Dijanić; Danijela Jurić Kaćunić; Jurica Matijević; Nada Galić (University of Zagreb. School of Dental Medicine, 2022)
Objectives: The aim of this study was to evaluate the retreatment duration and efficacy of eucalyptol and tea tree oil in engine driven and manual retreatment of epoxy resin based endodontic filling in extracted human teeth. Material and methods: Sixty human single rooted teeth were randomly divided into two groups. The first group was prepared using hand files, and the second one using Reciproc system. Root canals were filled with guttapercha points and AH Plus sealer. Retreatment was performed using K-reamers and Hedström files for the first group, and Reciproc instruments for the second group. Each group was divided into two subgroups (n=15) according to the retreatment solvent used (eucalyptol or tea tree oil). Root canals were longitudinaly split and analized with stereomicroscope (15x magnification). The surface of the remaining filling material was measured using an image processing software. Results: There were no statistically significant differences in the area of residual filling material among used solvents, nor in applied technique. Retreatment with Reciproc instruments was significantly faster compared to retreatment using hand files. The manual retreatment technique was faster when tea tree essential oil was used as a solvent compared to eucalyptol. Conclusions: Australian tea tree oil and eucalyptus oil were equally effective in removing endodontic filling material, but none of canals were completely free of the residual filling material. Retreatment with Reciproc instruments was faster compared to retreatment using hand files. The manual retreatment technique is faster when tea tree essential oil is used as a solvent compared to eucalyptol.